FREEDOM TO CHOOSE READING MATERIAL AND ITS EFFECTIVENESS TO READING COMPREHENSION - Mohamad Syafri; Hamka Hamka (IAIN Syekh Nurjati Cirebon, 2022)
This research elaborates readers’ independency to choose the reading material and its effectiveness towards reading comprehension. It highlights the correlation of students’ independency in deciding the reading material they are going to read and how it correlates with the reading comprehension. Reading is considered as one of the language skills with easier access to be developed, both in numbers and quality of the sources. The research is quasi-experimental research with 21 participants from reading class students in English Education Program of State Islamic University Datokarama Palu. During the six weeks meeting the students are divided into two groups: experimental group and control group. Treatment was given by giving students numbers of reading materials and let them choose and read freely. The data were then analysed quantitatively using independent sample t-test. The result of the test shows that the significant value is 0.309 or classified as no significance between the readers’ freedom to choose the reading material with their reading comprehension.